2011
DOI: 10.1590/s1516-35982011000300014
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × country interaction for weaning weight in the Angus populations of Brazil and Uruguay

Abstract: -It was analyzed the existence of genotype × environment interaction for weaning weight in populations of Angus from Brazil and Uruguay by using records of 73,205 animals (10,257 from Uruguay and 62,948 from Brazil) belonging to 33 and 161 farms and 13 and 34 regions in Uruguay and Brazil, respectively. It was used the one-and two-trait animal model analyses considering weight at weaning of each country as different characters. Coefficients of direct and maternal additivegenetic correlation estimated by two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
5
1
3
Order By: Relevance
“…These results are fairly consistent with the present findings. In comparison to present results, relatively less interaction effects were reported by Raidan et al (2015) for final weight with heritability values of 0.44 and 0.50, respectively for feedlot-raised and pasture-raised Nellore bulls while Espasandin et al (2011) reported similar direct heritability (0.35 and 0.34) for weaning weight in Asian J. Anim.…”
Section: Heritability For Growth Traitscontrasting
confidence: 95%
See 2 more Smart Citations
“…These results are fairly consistent with the present findings. In comparison to present results, relatively less interaction effects were reported by Raidan et al (2015) for final weight with heritability values of 0.44 and 0.50, respectively for feedlot-raised and pasture-raised Nellore bulls while Espasandin et al (2011) reported similar direct heritability (0.35 and 0.34) for weaning weight in Asian J. Anim.…”
Section: Heritability For Growth Traitscontrasting
confidence: 95%
“…Similarly, Bresolin et al (2015) reported that the genetic correlation for adjusted 205 days weight of Nellore bulls varied from 0.52-0.84 among three regions and Bradfield et al (1997) reported that the genetic correlation was 0.63 for weaning weight in Santa Gertrudis cattle between two production environments. Moreover, Espasandin et al (2011) found that the estimated genetic correlation for the direct additive genetic effect for weaning weight between two countries, Brazil and Uruguay, was 0.77. Theses results suggested that the best breeding bulls in one region or production system are not the same as in another region or production system.…”
Section: Estimates Of G×e For Growth Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…As médias das distribuições posteriores das correlações genéticas variaram de 0,54 a 0,78, para P210, e de 0,55 a 0,75 para GND. Da mesma forma que no presente estudo, evidências de interação GxA para características pré-desmama, em diversas raças bovinas, foram relatadas em outros trabalhos (Fridrich et al, 2005;Mascioli et al, 2006;Lopes et al, 2008;Zapata et al, 2010;Espasandin et al, 2011).…”
Section: Resultsunclassified
“…Concepts of stability, efficiency, and performance have been reported repeatedly in the debate concerning genetic improvement strategies and the success of breeding programs in diversifying environments (16,21) . However, the debate still stands on the fact that most breeding programs aim for improvements in productivity (15) , apparently disregarding the fact that the success of these programs require also the consideration of environmental traits (3) .…”
Section: Discussionmentioning
confidence: 99%